2012
DOI: 10.3892/ijmm.2012.1163
|View full text |Cite
|
Sign up to set email alerts
|

microRNA changes in the dorsal horn of the spinal cord of rats with chronic constriction injury: A TaqMan® Low Density Array study

Abstract: Elucidation of the mechanisms underlying neuropathic pain is expected to aid in the discovery and selection of effective therapeutic methods. Currently, microRNA (miRNA) is thought to play an important role in the development and maintenance of the nervous system. We, therefore, hypothesized that miRNAs are involved in neuropathic pain, and investigated this possibility by analyzing miRNA expression in the dorsal horn of the spinal cord in a chronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 34 publications
5
47
0
Order By: Relevance
“…This result is consistent with the study by Bin Yu et al, who showed that miR-21 and miR-221 were upregulated in the dorsal root ganglia after resection of the sciatic nerve in rats [30]. The study by Yuuki Genda et al also revealed that certain miRNAs, including miR-500, -221 and -21, were related to neuropathic pain in a chronic constriction injury rat model [31]. …”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with the study by Bin Yu et al, who showed that miR-21 and miR-221 were upregulated in the dorsal root ganglia after resection of the sciatic nerve in rats [30]. The study by Yuuki Genda et al also revealed that certain miRNAs, including miR-500, -221 and -21, were related to neuropathic pain in a chronic constriction injury rat model [31]. …”
Section: Discussionsupporting
confidence: 89%
“…Peripheral nerve injury not only produces changes in miR expression at the DRG, but also at the spinal cord (Genda et al, 2013) and brain (Arai et al, 2013; Hori et al, 2013). Hence, pain relevant miRs at any sensory level would potentially provide additional tools for the treatment of chronic neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In spinal nerve ligated rats, upregulation of miR-195 contributed to lip polysaccharide-induced expression of pro-inflammatory cytokines IL-1β, TNF-α, and iNOS in cultured microglia [78].Upregulation of miR-195 resulted in increased mechanical and cold hypersensitivity after PNI, whereas miR-195 inhibition reduced mechanical and cold sensitivity. Out of 111 miRNAs, 68% reported earlier and 32% related to the development of tumors of the nervous system and neurodegenerative diseases, few miRNAs, including miR-500, miR-221 and miR-21, relate to CCI-induced NP [79]. In another study miR-134, expression level found inversely related to MOR, the main transcript of μ-opioid receptor (MOR) gene expression [75].…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 97%